Ação e mediação cultural no contexto da biblioteca escolar: uma pesquisa bibliográfica na literatura biblioteconômica - FERREIRA, Andressa Pereira (2018)
The present work deals with cultural action and mediation in the perspective of the school library and in the transforming power that they can exert in this space. With the objective of clarifying how these actions can contribute to see the school library as a cultural production environment. Seeking to present the definitions of action and cultural mediation, also presented examples of cultural activities, which can be applied in the unit and contribute to the socioeducational development of students, focusing on the role of the librarian as a cultural agent. Emphasizing his academic background, essential to work in the cultural area. Concluding the research, it is considered that cultural actions are relevant instruments, which the library can make use of to improve its service and offer a leisure and entertainment environment for the user. Being pointed out the limitations of the research and indications for new ones, in order to enrich the theme "culture" in libraries.